Analisa Kebijakan Pemerintah di Kota Batam Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi - Patricia Angelina; Jolin , Jolin; Caroline Angelina; Selli , Selli; Stella , Stella; Elza Theofhilia (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
Based on the results of our group's research taking policies related to post-inflation risk in the Riau Islands region, there is the Batam, Riau Islands Province Economy, Riau Islands Province Batam inflation was recorded at 5.89% (yoy) in the second quarter of 2022. This figure increased by 3.24% (yoy) compared to the previous quarter as increased mobility, supply disruptions and geopolitical pressures have pushed up global commodity prices. Inflation in the second quarter of 2022 was influenced by an increase in inflation in the food, beverage and tobacco categories, which was triggered by an increase in the price of chicken eggs and various chili peppers. In addition, speed is affected by groups such as air freight fares and groups of food and restaurant suppliers.